Tumor Heterogeneity—A ‘Contemporary Concept’ Founded on Historical Insights and Predictions - Welch, Danny R. (Cancer research (Chicago, Ill.), 2016)
Heterogeneity is commonplace in all cancer types and at several levels—intrinsic (genetic), epigenetic, positional, and at the population level. The different subpopulations with a tumor mass communicate with each other and influence the behavior of other tumor cells both locally and at a distance. These properties have profound implications regarding the understanding of tumor behavior and how therapies are (or should be) administered. This brief commentary highlights the insightful review of Gloria Heppner and how it has influenced cancer research even three decades after it was published. Cancer Res; 76(1); 4–6. ©2016 AACR. See related article by Heppner, Cancer Res 1984;44:2259-65.